The future of Malaysia’s agriculture sector by 2030 / Thanusha Palmira Thangarajah and Suzilah Ismail - Thangarajah, Thanusha Palmira; Ismail, Suzilah (2021)
Agriculture is described as the art and science of developing the soil, growing crops, and raising livestock. Previously before the independence and until the early '80s, Malaysia was an agricultural country. However, the scenario has changed due to the rapid development of manufacturing and services sectors. Hence, the agriculture sector has been shrinking, and this is very alarming because the impact is very severe on our basic food production. Therefore, this study aims to forecast the agriculture sector by 2030 compared to the manufacturing and services sectors. Two forecasting techniques were used: Holt's Exponential Smoothing and Autoregressive Integrated Moving Average (ARIMA). The performances of the models were evaluated based on RMSE, GRMSE, and MAPE. The finding showed that the agriculture sector will decrease from 8.24% in 2021 to 6.20% by 2030. Thus, drastic strategic agricultural policy planning needs to be established and implement by incorporating modern technology in smart farming.